The role of motivational support in shaping the training activity of young athletes - Buhrii, Stanislav; Skrypka, Iryna; Chyzh, Viktor; Leshchenko, Hennadii; Kuryliuk, Serhii (SPORT TK-EuroAmerican Journal of Sport Sciences, 2026)
This study analyzed modern approaches to motivating young athletes based on Deci and Ryan’s self-determination theory, Dweck’s growth mindset theory, and Wallerand’s concepts of motivational profiling. Particular attention was paid to a critical analysis of traditional training methods that focus mainly on physical fitness and technical skills, often ignoring the specific psychological needs of young athletes. It is shown that effective motivation of athletes goes beyond a simple desire to win and includes intrinsic motivation, social and emotional competencies, psychological stability and creative thinking. A comparative analysis of international practices of working with talented young athletes, in particular the successful experience of the Scandinavian countries, was carried out. The influence of socio-economic factors on the development of sports talents and the problem of inequality of opportunities for children from low-income families was investigated. The modern possibilities of using digital technologies, adaptive learning and artificial intelligence to personalize the training process are considered. The importance of professional development of coaches and the need for their training to work with talented young athletes are emphasized. The study indicated the need to develop comprehensive motivational support programs that would take into account the individual needs of each athlete and contribute to the formation of a competitive generation of national sport.